2011
DOI: 10.1002/cjg2.1608
|View full text |Cite
|
Sign up to set email alerts
|

Research on Transient Electromagnetic Response of Magnetic Source in Borehole

Abstract: The transient electromagnetic exploration in borehole is a full space geophysical problem. The Gaver‐Stehfeest inverse Laplace transform is used to theoretically calculate the transient electromagnetic response in the receiver loop. And the effects of the parameters of the borehole mud, metal casing, the cement sheath and the formation on electromagnetic logging responses are analyzed. The response curves of different electrical conductivity of the borehole mud indicate that the borehole mud has little effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The transient electromagnetic method (TEM) is a time-domain electromagnetic exploration method that uses a step wave or pulse current as an excitation source to measure the pure secondary field after the primary field is turned off [1,2]. Due to the broadband nature of the emitted waveforms, which have high resolution, greater detection depth, sensitivity to good conductors, and less susceptibility to terrain limitations, TEM is widely applied in practical fields such as mineral resource exploration [3].…”
Section: Introductionmentioning
confidence: 99%
“…The transient electromagnetic method (TEM) is a time-domain electromagnetic exploration method that uses a step wave or pulse current as an excitation source to measure the pure secondary field after the primary field is turned off [1,2]. Due to the broadband nature of the emitted waveforms, which have high resolution, greater detection depth, sensitivity to good conductors, and less susceptibility to terrain limitations, TEM is widely applied in practical fields such as mineral resource exploration [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, finite element analysis is undertaken to identify the extent of loading deformation of 3D frame model of High-precision instrumented indentation tester [5][6][7][8] which has been developed and realized by us. It is found that the value of frame inclination angle is directly proportional to the working load.…”
Section: Introductionmentioning
confidence: 99%